O impacto do distanciamento social na vida acadêmica: : experiências de estudantes de ciências biológicas - dos Anjos Almeida, João Victor; Gimenez da Silva Augusto, Thais (Góndola, enseñanza y aprendizaje de las ciencias, 2025)
The SARS-CoV-2 pandemic required abrupt changes in university life, with campus closures and the transfer of classes to digital platforms. This transition exposed inequalities in access to the internet and equipment, in addition to affecting students’ emotional and social dimensions. This study analyzed the perceptions of Biological Sciences undergraduates during and after the period of social restrictions, using questionnaires and a focus group, integrating quantitative and qualitative data. The results indicated decreased motivation, difficulties in concentration, high levels of anxiety, and a sense of learning loss. Among the most frequently mentioned aspects were the absence of laboratory and field practices, the lack of interaction with peers and professors, and the disorganization of routines—factors that contributed to mental exhaustion and widespread discouragement. The research participants were students at different stages of the program, which made it possible to observe contrasts: first-year students without prior in-person experience and senior students who compared their previous and subsequent experiences of isolation. The return to in-person activities promoted improvements in engagement and well-being, attributed to human interaction and campus life, with reports of increased motivation, belonging, and emotional recovery. It is concluded that, although digital resources ensured continuity, they do not replace the formative value of the physical environment, reinforcing the relevance of hybrid models that integrate technology, in-person practices, and psychosocial support.